Gender-Specific Differences in Diastolic Dysfunction and HFpEF: Pathophysiology, Diagnosis, and Therapeutic Strategies - Francesca Coppi; Gianluca Pagnoni; Francesca Grossule; Ashraf Nassar; Arianna Maini; Giuseppe Masaracchia; Francesco Sbarra; Elisa Battigaglia; Enrico Maggio; Daniela Aschieri; Federica Moscucci; Marcello Pinti; et al. (Journal of Cardiovascular Development and Disease)
: Heart failure with preserved ejection fraction (HFpEF) accounts for approximately 50% of heart failure cases and is primarily characterized by impaired diastolic function, leading to increased ventricular filling pressures and symptoms like dyspnea and reduced exercise tolerance. Significant gender-specific differences are observed, with women, particularly post-menopausal, experiencing higher prevalence and distinct clinical profiles compared to men. Diastolic dysfunction in HFpEF involves altered cellular mechanisms such as reduced SERCA2a expression, impacting calcium handling and myocardial relaxation. Diagnostic strategies mainly employ echocardiography, including Doppler imaging, tissue Doppler imaging, and strain imaging, to assess ventricular relaxation and stiffness. However, early identification remains challenging, necessitating advanced tools like cardiac magnetic resonance and exercise stress testing for accurate diagnosis, especially in women who often present with subtle symptoms. Treatment options for HFpEF have traditionally been limited, but recent trials, notably EMPEROR-PRESERVED and DELIVER, demonstrated significant cardiovascular benefits using sodium–glucose cotransporter-2 (SGLT2) inhibitors. Additionally, glucagon-like peptide-1 receptor agonists (GLP-1 RAs) have shown promising results, particularly in obese patients. Despite these advances, gender differences in therapeutic response necessitate further research for personalized management strategies. Understanding sex-specific pathophysiological mechanisms and optimizing diagnostic criteria remain essential to improving prognosis and quality of life in HFpEF patients.